Alamat ng ilang-ilang The legend of the ylang-ylang - Matias, Segundo D. (Lampara books, 2013)
"In the old days, there was a datu's daughter named Ilang. Aside from beauty, Ilang also possessed her father's heroism and bravery. But if she was a success in warfare, she was a failure in the realm of love. Find out in this story the origin of the fragrant ylang-ylang--and how a failure can be turned into a significant goal."